DEVELOPING RELIGIOUS MODERATION IN STATE ISLAMIC RELIGIOUS COLLEGE INDONESIA: TEXT AND CONTEXT-BASED UNDERSTANDING OF ISLAM - Wardani, Yaniah; Siti Sajaroh, Wiwi; Suprapto (Jurnal Adabiyah, 2022)
The presence of religious moderation in Indonesian society with the emergence of radical groups has become hope for people who crave a comfortable life in religion. This paper aims to find out how students understand the text (verses of the Qur'an and Hadith) according to the context of religious moderation. In addition, how to prevent the emergence of Radicalism and provide solutions to academics in developing an attitude of religious moderation in Indonesia. The method used in this study is a mixed method, namely by using qualitative and quantitative research. Qualitative research is carried out by reviewing various literatures, in-depth interviews, participating in observations, and FGDs with resource persons who are experts in their fields. While quantitative research uses Linear Regression Analysis through IBM SPSS data processing which is the strengthening data from the literature study on Text-Based and Context-Based Islamic Understanding in Developing Religious Moderation in State Islamic Higher Education which was carried out in five universities in Indonesia. This study aims to get a positive response from the UIN academic community about the importance of understanding religious moderation. This is based on the results of the T-test and description of the data which shows that students have the same perception in responding to the statements presented in the results of surveys, interviews, and FGDs. The implementation strategy is to socialize the understanding of religious moderation based on the text and context in the curriculum and the importance of establishing religious moderation institutions/schools on campus. الملخص أصبح وجود الاعتدال الديني في المجتمع الإندونيسي مع ظهور الجماعات المتطرفة أملًا للأشخاص الذين يتوقون إلى حياة مريحة وصحية في الدين. تهدف هذه الورقة إلى معرفة كيفية فهم الطلاب للنص (آيات من القرآن والحديث) وفقًا لسياق الوسطية الدينية. إلى جانب ذلك ، كيفية منع ظهور الراديكالية وتقديم الحلول للأكاديميين في تطوير موقف الاعتدال الديني في إندونيسيا. الطريقة المستخدمة في هذه الدراسة هي الطريقة المختلطة ، أي باستخدام البحث النوعي والكمي. تم إجراء بحث نوعي من خلال مراجعة الأدبيات المختلفة ،والمقابلات المتعمقة ، والمشاركة في الملاحظات ، وعمل مجموعات التركيز مع أشخاص ذوي خبرة في مجالاتهم. بينما استخدم البحث الكمي تحليل الانحدار الخطي من خلال معالجة بيانات IBM SPSS والتي أصبحت البيانات المعززة من الدراسات الأدبية حول التفاهم الإسلامي القائم على النص والقائم على السياق في تطوير الاعتدال الديني في الكلية الدينية الإسلامية التابعة للدولة ، والتي تم إجراؤها في خمس جامعات في إندونيسيا . يهدف هذا البحث إلى الحصول على رد إيجابي من المجتمع الأكاديمي التابع لكلية الدين الإسلامي في الدولة الإسلامية حول أهمية فهم الوسطية الدينية. ويستند إلى نتائج اختبار T وأوصاف البيانات التي تظهر أن الطلاب لديهم نفس التصور في الاستجابة للبيانات المقدمة في الاستطلاعات والمقابلات ونتائج مجموعات النقاش المركزة. تتمثل استراتيجية التنفيذ في إضفاء الطابع الاجتماعي على فهم الاعتدال الديني بناءً على النص والسياق في المناهج الدراسية وأهمية إنشاء مؤسسات / مدارس للاعتدال الديني .في الحرم الجامعي